Analisis Karakteristik dan Kebutuhan Parkir di Pasar Bambu Kuning Bandar Lampung - prambudi, agung; Sulistyorini, Rahayu; Putra, Sasana (Universitas Lampung, 2021)
Parking is a temporary condition of not moving a vehicle. One of the parking requirements is Pasar Bambu Kuning Bandar Lampung. However, they prefer to park on the shoulder of the road and cause congestion around the market. The purpose of this study was to determine and analyze the characteristics of parking at Pasar Bambu Kuning in Bandar Lampung and to analyze the capacity and needs of parking spaces at Pasar Bambu Kuning in Bandar Lampung. The results showed that the highest frequency of four-wheeled vehicles was 395 vehicles / 3 hours, while the highest frequency of two-wheeled vehicles was 653 vehicles / 5 hours in on-street conditions. The highest parking turnover rates for four-wheeled and two-wheeled vehicles are 1.518 vehicles / SRP / hour and 0.445 vehicles / SRP / hour, respectively, then the highest parking index values for four-wheeled and two-wheeled vehicles are 144% and 72.5%, respectively. . The maximum parking capacity for four-wheeled and two-wheeled vehicles is 281 vehicles / hour and 618 vehicles / hour respectively and the parking requirements for four-wheeled and two-wheeled vehicles are 73 SRP and 82 SRP. Keywords: parking, parking accumulation, frequency, average duration, cumulative frequency, turnover rate, parking capacity, parking demand.